Simple, secure, and lightweight mechanism for mutual authentication of nodes in tiny wireless sensor networks. (10th March 2020) - Jain, Usha; Hussain, Muzzammil; Kakarla, Jagadeesh
Summary: Wireless sensor networks (WSNs) are widely used in large areas of applications; due to advancements in technology, very tiny sensors are readily available, and their usage reduces the cost. The mechanisms designed for wireless networks cannot be implied on networks with tiny nodes due to battery and computational constraints. Understanding the significance of security in WSNs and resource constraintness of tiny WSNs, we propose a node authentication mechanism for nodes in wireless sensor networks to avoid security attacks and establish secure communication between them. In the proposed mechanism, a base station (BS) generates a secret value and random value for each sensor node and stores at the node. The sensor node authenticates using secret value and random number. Random nonce ensures freshness, efficiency, and robustness. The proposed mechanism is lightweight cryptographic, hence requires very less computational, communication, and storage resources. Security analysis of the proposed mechanism could not detect any security attack on it, and the mechanism was found to incur less storage, communication, and computation overheads. Hence, the proposed mechanism is best suitable for wireless sensor networks with tiny nodes. Abstract : In this, we have proposed a mutual node authentication mechanism for tiny wireless sensor networks (WSNs). The proposed mechanism uses lightweight operations like exclusive OR (XOR) and one‐way hash; it is secure, lightweight, and most suitable for tiny networks. The proposed mechanism is proved to be secure and also consumes very less resources compared to the existing mechanisms.